2020
DOI: 10.1371/journal.pone.0229255
|View full text |Cite
|
Sign up to set email alerts
|

Exploring sexual dimorphism of the modern human talus through geometric morphometric methods

Abstract: Sex determination is a pivotal step in forensic and bioarchaeological fields. Generally, scholars focus on metric or qualitative morphological features, but in the last few years several contributions have applied geometric-morphometric (GM) techniques to overcome limitations of traditional approaches. In this study, we explore sexual dimorphism in modern human tali from three early 20th century populations (Sassari and Bologna, Italy; New York, USA) at intra-and interspecific population levels using geometric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 73 publications
1
30
0
Order By: Relevance
“…Sex differences in the navicular articular surface of the talus have been reported by Ferrari et al [17], who indicated that the female navicular articular surface of the talus was more twisted in the frontal plane and more curved than that in males. In contrast, a recent geometric morphometric studies [18][19][20] has not detected sex differences in the articular surface orientation of the talus. Hence, based on these previous studies, the sex-and age-related differences in the articular morphology of the talus are still under debate.…”
Section: Introductionmentioning
confidence: 71%
“…Sex differences in the navicular articular surface of the talus have been reported by Ferrari et al [17], who indicated that the female navicular articular surface of the talus was more twisted in the frontal plane and more curved than that in males. In contrast, a recent geometric morphometric studies [18][19][20] has not detected sex differences in the articular surface orientation of the talus. Hence, based on these previous studies, the sex-and age-related differences in the articular morphology of the talus are still under debate.…”
Section: Introductionmentioning
confidence: 71%
“…Sex differences in the navicular articular surface of the talus have been reported by Ferrari et al [17], who indicated that the female navicular articular surface of the talus was more twisted in the frontal plane and more curved than that in males. In contrast, a recent geometric morphometric studies [18][19][20] has not detected sex differences in the articular surface orientation of the talus. Hence, based on these previous studies, the sex-and age-related differences in the articular morphology of the talus are still under debate.…”
Section: Introductionmentioning
confidence: 76%
“…Therefore, the stepwise selected measurements were analysed by leave-one-out cross-validation linear discriminant analysis (LDA), using final discriminant functions to predict the sex of the MLC. Finally, the MLC was projected into the Principal Component Analysis (PCA) previously computed on the known sample to explore its proximity with one sex or the other, as already done with other bones [ 27 ]. The cranial metric dataset was analysed in R v. 3.6.2 [ 28 ].…”
Section: Methodsmentioning
confidence: 99%